Severe COVID-19 pneumonia in Piacenza, Italy — A cohort study of the first pandemic wave. Issue 2 (February 2021) - Guglielmetti, Lorenzo; Kontsevaya, Irina; Leoni, Maria C.; Ferrante, Patrizia; Fronti, Elisa; Gerna, Laura; Valdatta, Caterina; Donisi, Alessandra; Faggi, Alberto; Paolillo, Franco; Ratti, Giovanna; Ruggieri, Alessandro; et al.
Abstract: Background: Piacenza is the closest city to the first coronavirus disease 2019 (COVID-19) cluster in Italy and has the highest national COVID-19 death rates per population. The objective of this study is to present characteristics and outcomes of patients admitted to medical departments of the Hospital of Piacenza during the first wave of the epidemic. Methods: A total of 218 patients with confirmed or suspect COVID-19 and severe pneumonia were included from February 21st to May 15th, 2020. Routinely-collected clinical and laboratory data were retrospectively retrieved from electronic medical files. A Cox proportional-hazards model was fit to assess the association of treatment and other variables with death. Results: Median age of patients was 68 years; 150 patients (69%) had comorbidities, mainly hypertension (107, 49%). Overall, 185 (85%) patients had acute respiratory distress syndrome (ARDS) on admission, including 103 (47%) with moderate or severe ARDS. Chest computed tomography scan showed bilateral disease in 201 (98%) and extensive lung involvement in 79 (50%) patients. Most patients received antiviral treatment (187, 86%) and corticosteroids (134, 61%). All patients received respiratory support and 64 (29%) were admitted to intensive care unit. As of June 30th, 100 patients (46%) died, 109 patients (50%) were discharged, and 9 patients (4%) were still hospitalized. In multivariable Cox analysis, age above 65 years, having more than one comorbidity, severe ARDS, low platelet counts, and high LDH levels at admission were associated with mortality, while having diarrhea at admission was associated with survival. The use of antivirals or corticosteroids was not associated with survival. Conclusions: Overall case fatality rates were high and associated with comorbidities, extensive lung involvement, ARDS at admission, and advanced age. The use of antivirals was not associated with increased survival.